Consider the following prime factorization :
where and are both 3 - digit prime numbers, then enter the value of .
Bonus : Prove it algebraically .
Source : JMO sample paper (2015)
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = 9 x 4 + 9 x 3 + 8 x 2 + 9 x + 9 such that f ( 1 0 ) = 9 9 8 9 9 .
Now we will factorize f ( x ) as follows f ( x ) = x 2 ( 9 x 2 + 9 x + 8 + x 9 + x 2 9 )
= x 2 [ 9 ( x 2 + x 2 1 ) + 9 ( x + x 1 ) + 8 ] N o w s e t ( x + x 1 ) = t ⟹ x 2 + x 2 1 = t 2 − 2 (Squaring both sides) ⟹ Substituting in f(x) and factorising we get : ⟹ f ( x ) = x 2 [ ( 3 t − 2 ) ( 3 t + 5 ) ] ⟹ f ( x ) = x 2 [ 3 ( x + x 1 ) − 2 ] [ 3 ( x + x 1 ) + 5 ] ⟹ f ( x ) = ( 3 x 2 − 2 x + 3 ) ( 3 x 2 + 5 x + 3 ) ⟹ f ( x ) = g ( x ) ⋅ h ( x ) (Say) ⟹ N o w 9 9 8 9 9 = f ( 1 0 ) = g ( 1 0 ) ⋅ h ( 1 0 ) = 2 8 3 × 3 5 3
Hence , a + b + c + d = 1 8